EVALUATION OF THE IMPACT OF SCHOOL-BASED DYSMENORRHEA EDUCATION ON CHANGES IN KNOWLEDGE ANDPERCEPTION OF FEMALE STUDENTS AT STATE SENIOR HIGHSCHOOL 1 KEDIRI: EVALUASI DAMPAK EDUKASI DISMENORE BERBASIS SEKOLAHTERHADAP PERUBAHAN PENGETAHUAN DAN PERSEPSI SISWI SMA NEGERI 1 KEDIRI - Rassya Bunga Maharani; Aisyah Febrianti Wicaksono; Amanda Chiquita Putri; Digea Pramita Akbar; Muhammad Nurul Ghofar; Rivaldy Prayudha Trivana Eksipierwilest; Arshy Prodyanatasari (PT. ROCE WISDOM ACEH, 2026)
Menstrual pain (dysmenorrhea) is pain accompanied by abdominal cramps. This activity aims to increase students’ knowledge about managing dysmenorrhea without medication through interactive education. The design used is a single-group pre-experimental design with pretest and posttest, using PowerPoint and leaflets as media. Education was provided to 22 tenth-grade students at SMA Negeri 1 Kediri for 40 minutes. Statistical analysis was performed using SPSS software version 27. Data analysis included inferential statistical tests, specifically the Wilcoxon Signed-Rank Test, to assess differences in knowledge scores before and after the intervention. The Wilcoxon Test results showed a change in scores after the intervention, with a larger average increase (10.28) than the average decrease (8.72). These findings indicate that the intervention affected changes in respondents’ pretest and posttest results. The highest level of understanding was found in the material on the definition of menstruation and non-medical ways to reduce menstrual pain. In contrast, the material on the causes of primary dysmenorrhea and the timing of consultation with health workers still needs strengthening. This education is effective in increasing adolescents’ independence in managing menstrual pain without medication and is recommended forintegration into school health unit (SHU) activities.